The effect of a novel toothpaste in children with white spot lesions - Yilmaz, Muesser Ahu; Kulan Yildiz, Pinar; Gokkaya, Berna; Ozsalih Bilsel, Seda; Kargul, Betul (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the effect of a novel mineral containing toothpaste in comparison to a fluoride toothpaste in children with white spot lesions. Method: The clinical study was conducted from 2016 to 2018 at Marmara University Department of Pediatric Dentistry Clinic after approval from the ethics review committee of Yeditepe University, Istanbul, Turkey, and comprised children of either gender aged 4-5 years having white spot lesions. They were randomly allocated into two groups. The FT ( Fluoridated Toothpaste ) group was given a 500ppm fluoridated toothpaste, while the Mineral Containing Toothpaste (MCT) group was given toothpaste containing calcium glycerophosphate, magnesium chloride, and 12% xylitol. The white spot lesions were examined using Laser Fluorescence (LF) at baseline and after a month of usage. The two readings were compared. Stimulated saliva was collected for measuring the salivary potential of hydrogen, buffering capacity, and streptococcus mutans. Data was analysed using SPSS 19. Results: Of the 26 children, 10(38%) were girls and 16(62%) were boys. The overall mean age was 4.77+/-0.54 years. There were 13(50%) subjects in each of the two groups. Of the 381 measurements done, 198(52%) were in the MCT group and 183(48%) in the FT group. LF scores decreased in both the groups (p=0.001). The remineralising potential was not significantly different (p=0.866), while salivary buffering capacity and potential of hydrogen increased in both the groups but the change was not significant (p>0.05). The number of children positive for streptococcus mutans decreased in both the groups (p>0.05). —Continue